Evaluating complications of self-intake of abortion pills among reproductive age group women - Dodiya, Diptika; Shah, Maitri; Nagdev, Neethi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Abortion is termination of the pregnancy before the period of viability. Induced abortion in most of the cases, is an outcome of unwanted pregnancy. Unsafe abortion is “The termination of unintended pregnancy either by persons lacking the skills or lacking minimum medical standards or both.” and it is strongly associated with Complications. The objective of the study was to evaluate different types of complications (incomplete abortion, failed abortion, septic abortion, ectopic pregnancy) among women with self-intake of abortion pill among women of reproductive age group. Methods: 70 reproductive age group women with history of self-intake of abortion pills within a period of last one month were included in the study. Socio demographic characteristics, obstetric and menstrual history of these women was recorded. This was followed by diagnosis with help of clinical and transvaginal sonography of these women. All of them were managed according to their diagnosis. Their reply was recorded in pre structured performa. Results: Majority (70%) presented with incomplete abortion requiring surgical evacuation. Anemia was most common associated co-morbidity in women and 17% women required blood transfusions. Four percentage women presented with life threatening shock. Sepsis was noted in 3% of women. Conclusions: Incomplete abortion was the major complication after self-intake of abortion pills which had resulted into blood transfusion in 17% of the cases.